Desperation - King, Stephen (New York : Viking, 1996)
Several cross-country travelers--including a writer, a family on vacation, and a professor and his wife--end up in the little mining town of Desperation, where a crazy policeman and evil forces compel them to fight for their lives.
Keywords: Traffic police -- Fiction; Psychological fiction